Giant thymic carcinoid. Issue 787 (May 1991) - John, L. C.; Hornick, P.; Lang, S.; Wallis, J.; Edmondson, S. J.
Abstract : Thymic carcinoid is a rare tumour. It may present with ectopic endocrine secretion or with symptoms of compression as a result of its size. A case is reported which presented with symptoms of compression where the size of the tumour was uniquely large such as to warrant the term giant thymic carcinoid. The typical histological features are described, together with its possible origin and its likely prognosis.